The Response to Dietary Leucine in Laying Lens - Sakomura, Nilva Kazue [UNESP]; Reis, Matheus; Bonagurio, Lucas Pimentel [UNESP]; Leme, Bruno Balbino [UNESP]; Viana, Gabriel Silva; Melaré, Mirella Cunha [UNESP]; Gous, Robert Mervyn (MDPI, 2023)
This study aimed to estimate the standardized ileal digestible leucine intake (SID-Leui, mg) in laying hens for maintenance, and to describe the response in laying hens to SID-Leui, thereby providing the information required to determine the optimum economic intake of SID-Leu for laying hens. Two nitrogen balance series, one balanced and the other unbalanced with respect to leucine (Leu), were used to estimate the SID-Leu requirement for maintenance using 36 roosters per series. The roosters were randomly distributed among the six levels of Leu with each level being replicated six times. The six diets were formulated to contain 0.0, 3.5, 6.9, 10.4, 13.9, or 17.4 g/kg of SID-Leu for the unbalanced series and 0.0, 4.0, 8.0, 12.0, 16.0, or 20.0 g/kg of SID-Leu for the balanced series. The SID-Leui maintenance requirement was calculated as 144 mg/bird d, 66 mg/kg d, 74 mg/kg0.75d or 395 mg/BPm0.73d. For the response trial, 120 individually caged laying hens (63 weeks old) were randomly distributed among eight treatments with 15 replicates. To estimate the SID-Leui for the population of hens, the Reading Model was fitted to the data using body weight (BW, kg), SID-Leui and egg output (EO, g). The Reading Model calculated the mg SID-Leui = 11.6 EOmax + 43.4 BW. The efficiency of SID-Leu utilization for laying hens was estimated to be 79%.
Keywords: amino acids; dilution technique; efficiency of utilization; egg output; reading model